Correlación entre la frecuencia de cocinar y el consumo de agua potable - Christian Mauricio, Yuquilema Alvarado (2020)
The Ecuadorian Standard CPE INEN 005-9-1, used for the design of drinking water systems, recommends qualitative research on consumption habits and water use in order to establish allocations that satisfy user demand, avoiding non-discretionary use through optimal design. The objective of the research is to provide current data that will make it possible to reduce the lack of knowledge of the consumption qualities of a population, considering socioeconomic strata and population size. It is assumed that the frequency of cooking in each house in the residential sector is one of the activities that consumes the most water, so a statistically valid equation is sought to corroborate and explain the supposed correlation. The half-yearly drinking water consumption data per capita for 11 cities with populations of up to 150,000 inhabitants were grouped by cities in socioeconomic strata A, B, C and D and by their small, medium and large population size; this was done prior to the graphic and statistical analysis of uni and multifactorial linear regression between the variables of drinking water use and consumption. In the graphical and statistical analysis, the results in the first instance show some strong correlations between the variables, but are discarded for not having statistical validity. The regression analyses confirm that there is no correlation that allows the generation of a linear model. Therefore, the variation in the consumption of drinking water is due to other types of habits that make use of it.